WIRELESS DATA TRANSMISSION HSPAAND LTE IN THE MANAGEMENT AND INFORMATION SYSTEMS (Perner's Contacts, 2013)
The article deals with the development and features of UMTS networks, evaluating the properties of public mobile networks T-Mobile, Telefónica and Vodafone on the basis of experimental measurements and the possibility of use in traffic control and information systems.
Keywords: HSDPA; HSPA; HSUPA; LTE; UMTS; response; connection speed; download; upload; standard deviation